Storytelling no cenário jurídico: uma análise sob a perspectiva da mediação da informação - Barreto, Rayara Bastos (2023)
This research dialogues with Information Science (CI), Law and Literature. Its general objective is to analyze the contributions of storytelling in the construction of legal narratives. Its specific objectives are: to identify the most used models in the specialized literature of legal narrative; investigate the literary works that can be used in the construction of these legal narratives; and check the work on storytelling produced in the area of Information Science. The methodological perspective is based on a social bias, using a qualitative approach. As research methods, bibliographic research and documentary research were used. The first was used in the databases of the National Postgraduate Research Council (Conpedi), in the Reference Database of Articles and Journals in Information Science (Brapci) and in the Portal of Journals of the Coordination for the Improvement of Level Personnel Superior (Capes); the second was used on the website of the Court of Justice of the State of Ceará. As for data analysis, content analysis was adopted, with the establishment of two categories: storytelling resources and information mediation. The results demonstrate that there is an operationalization of storytelling in the legal sentence, through poetry and in scientific communication with the adoption of literary works, aiming at clarifying the language. It is concluded that storytelling contributes to the accessibility of procedural discourse, however it lacks incentive actions in favor of promoting this art in the academic legal scenario.